Using Monte Carlo Simulation as a Financial Modeling Tool to Support Sustainability Efforts of a Government Agency. - Leggio, K. B.
The National Oceanic and Atmospheric Administration (NOAA) collects ecosystem data to support coastal resource conservation and management activities by studying stressors that impact estuaries such as the Chesapeake Bay, which is the largest in the United States. This paper seeks to help NOAA justify its existence and its budget by utilizing Monte Carlo simulation as a financial modeling tool, with such simulations providing insights on how to allocate identified resources. The results of the study offer an innovative method for helping government managers decide how much money to spend, what to spend it on, and how to acquire resources for the Chesapeake Bay Interpretive Buoy System. Moreover, this paper also demonstrates how an experiential project in graduate business education can be used to support sustainability efforts by addressing community-focused issues while improving student connection between theory and application at the same time.